Heroic and Humane Entrepreneurs: Identity Work in Entrepreneurship Education - Hytti U; Heinonen J (Emerald, 2022)
Purpose - The paper investigates the identity work of postgraduate students participating in an entrepreneurship training programme for life sciences. The study aims to analyse what kind of entrepreneurial identities are constructed and in what ways in the context of the programme.
Design/methodology/approach - The study relies on learning diaries and other written materials harvested from seven participants. Drawing on a social constructivist analysis, the materials were analysed by drawing attention to the kind of identities created, the contradictions that surfaced and how those were resolved in the written materials.
Findings - Two distinct entrepreneurial identities were constructed by the participants: the heroic and the humane. The first is the stereotypical role prototype that the participants experiment with. For the male participants this seems acceptable and normal. If they were in possession of more information, knowledge and skills they could identify with this heroic entrepreneurial identity. However, the female participants constructed an alternative identity; the humane entrepreneur running a low-tech firm with modest business goals or acting as an intrapreneur in an existing organization.
Research implications - Future research should consider entrepreneurship programmes as arenas for (gendered) identity work.
Practical implications - Entrepreneurship training should not only provide the participants with business knowledge and skills but facilitate their entrepreneurial identity work.
Originality/value - This study contributes to understanding entrepreneurship education as a context for entrepreneurial identity construction and extends our understanding of the expected outcomes of entrepreneurship education programmes. The study demonstrates how entrepreneurial identity construction processes in the context of entrepreneurship training are gendered.